Longitudinal Prevalence of Antibodies to Endemic Pathogens in Bulk Tank Milk Samples From Dairy Herds Engaged or Not in Contract Heifer Rearing - McCarthy, Marie-Claire; O'Grady, Luke; McAloon, Connor G.; Mee, John F. (Frontiers in Veterinary Science, 2021)
Since the abolition of EU milk quotas in 2015, Europe’s dairy industries have undergone rapid expansion with possible resultant increased inter-herd transmission of endemic pathogens. The aims of this study were 1) to establish the post-2015 prevalence of antibodies to selected endemic infectious diseases and 2) to determine if prevalences differed between herds where heifers were reared at home and those where heifers were sent out for contract-rearing. Three bulk tank milk (BTM) samples were collected annually between May and August of 2018-20 inclusively from 120 Irish dairy herds. Additionally, herd vaccination status was collected by questionnaire. Milk samples were tested using commercially available ELISAs for eight pathogens: bovine viral diarrhoea virus (BVDV), bovine herpesvirus 1 (BoHv-1), bovine respiratory syncytial virus (BRSV), Mycoplasma bovis, Mycobacterium avium subspecies paratuberculosis (MAP), Salmonella Dublin (S. Dublin), Leptospira Hardjo (L. Hardjo) and Neospora caninum (N. caninum). The true prevalence of each pathogen was calculated using a Rogan-Gladen estimator. The true prevalences (95% CI) of BTM antibodies in unvaccinated herds across the three years were as follows (i) BVDV: 57, 86 and 73% (95% CI 40.7-65.9, 74-94, 58-85) (n= 56, 56, 48) (ii) BoHv-1: 47, 49 and 19% (95% CI; 26.3-69.7, 25-75, 1-56) (n = 21, 20, 11) (iii) L. Hardjo: 34, 59 and 73% (95% CI; 12.5–63, 33-82, 33-99) (n = 15, 21, 10) (iv) S. Dublin 32, 57 and 11% (95% CI; 12.21- 68.1, 30.2-90.1, 0) (n=19, 22, 13) (v) BRSV: 100% (95% CI; 99.5-100, 100, 100) (n = 120, 109, 91) (vi) MAP: 0% (95% CI; 0, 0, 0) (n= 120, 109, 91) (vii) N. caninum 0% (95% CI; 0, 0, 0) (n=120, 109, 91) and (viii) M. bovis (ELISA) 53, 0.42 and 30% (95% CI; 3.95-6.84, 0, 21-41) (n=120, 109, 91). M. bovis was detected by PCR in 0, 1 and 0% of herds in 2018, 2019 and 2020, respectively. This study showed that expanding Irish dairy herds are endemically infected with several of the studied pathogens. No differences in herd prevalence of infectious agents were observed between farms with different heifer rearing strategies (contract-rearing versus traditional rearing).